Characteristics of Ba(Zr0.1Ce0.7Y0.2)O3-δ nano-powders synthesized by different wet-chemical methods for solid oxide fuel cells. Issue 1 (January 2018) - Min, Sung Hwan; Lee, Jin Goo; Jeon, Ok Sung; Park, Myeong Geun; Ryu, Kwang Hyun; Myung, Jae-ha; Shul, Yong-Gun
Abstract: Ba(Zr0.1 Ce0.7 Y0.2 )O3-δ nano-particles were prepared by different wet-chemical synthesis, Pechini (BZCY(P)) and co-precipitation (BZCY(C)), respectively. The BZCY(C) powders have a particle size in range of about 50–150 nm, which is smaller than the BZCY(P) powders with about 500–900 nm. Both the BZCY materials show perovskite structures, but there are impurities in the BZCY (P). Moreover, the electrolyte density was higher in the BZCY (C) than the BZCY (P). The single cells with BZCY (C) electrolytes exhibited about 0.23 W cm −2 at 600 °C and about 0.31 W cm −2 at the same temperature were obtained when the anode-functional layer was introduced between the anode and electrolyte. Thus, the BZCY prepared by carbonate-derived co-precipitation method can be more favorable for high-purity and dense electrolytes in the solid oxide fuel cells than the BZCY prepared by Pechini method.